The impact of angling on smallmouth and largemouth yellowfish, labeobarbus aeneus and labeobarbus kimberleyensis, in Lake Gariep, South Africa - Ellender, Bruce Robert (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2009)
A large sportfishery that targets both smallmouth (Labeobarbus aeneus) and largemouth (Labeobarbus kimberleyensis) yellowfish exists in South Africa. Both species have high conservation priority, and no assessments documenting the effect of angling on L. aeneus and L. kimberleyensis have been undertaken. The overall aim of this study was to provide an assessment of the impact of angling on L. aeneus and L. kimberleyensis. The specific objectives of this study were to characterise the sectors utilising Lake Gariep, document catch, effort and total catch for the fishery as well as the locality specific biology of L. aeneus and L. kimberleyensis. The study was undertaken on Lake Gariep, South Africa's largest impoundment, situated on the Orange River system in central South Africa. Subsistence fishers were the dominant user group, constituting 60 % of the fishery, the remainder constituted recreational anglers. Angler catches were dominated by carp (Cyprinus carpio; 74 %), followed by mudfish (Labeo capensis; 13 %) and smallmouth yellowfish (8 %). Catches of largemouth yellowfish contributed < 0.5 % to the total catch. The relative abundance of species by weight differed by area (Ï‡Â² test of independence: Ï‡Â² = 182, df = 4, p â‰¤ 0.05). On any sampling day time fished was the best predictor for differences in probability of capture (PC) (Wald XÂ²(1) = 7.169, p = 0.007). The probability of capturing L. aeneus differed significantly between month (Wald XÂ²(5) = 20.690, p = 0.000) and region (Wald XÂ²(3) = 46.755, p = 0.000). The single best predictor of differences in log abundance and non-zero CPUE was region (Factorial ANOVA p â‰¤ 0.05). Mean CPUE ranged from 0.21 Â± 0.06 kg. manâ »Â¹.hrâ »Â¹ to 0.82 Â± 0.11 kg. manâ »Â¹.hrâ »Â¹ in the OV region and 0.42 Â± 0.10 kg. manâ »Â¹.hrâ »Â¹ to 1.17 Â± 0.24 kg. manâ »Â¹.hrâ »Â¹ in the GD region. Angler effort was higher in OV than in GD and ranged from 17 Â± 3 anglers/day to 45 Â± 9 anglers/day and 6 Â± 1 anglers/day to 41 Â± 8 anglers/day, respectively. Total catch was higher in the GD 46.0 [95 % CI = 15:102.6] t. periodâ »Â¹ than the OV region 40.0 [95 % CI = 13.9:89.6] t. periodâ »Â¹. The total catch from the Lake Gariep fishery between March and December 2007 was estimated to be 86.0 [95 % CI = 40.4:154.8] t. periodâ »Â¹. Age and growth was determined using whole otoliths. The growth of L. aeneus was best described by the von Bertalanffy growth model as Lt = 481.80 (1- eâ »Â°Â·Â²Â²â ½tâ ºÂ°Â·â ¶Â¹â ¾). Gonadal development for L. aeneus was seasonal, with the gonadosomatic index peaking in January, revealing a distinct spawning season. The length at 50 % maturity for female L. aeneus was attained at a fork length of 354.7 mm. Natural mortality (M) was estimated at 0.55 yearâ »Â¹. The growth of L. kimberleyensis was described by the von Bertalanffy growth model as Lt = 763.22 (1- eâ »Â°Â·Â¹Â¹â ½tâ ºÂ°Â·â ¶Â³â ¾). Only 6 mature female and 15 mature male L. kimberleyensis were recorded during the study period. The smallest mature female was a 390 mm FL stage four female and the earliest recorded mature male was a 337 mm FL, ripe running male. Natural mortality (M) was estimated at 0.08 yearâ »Â¹ for L. kimberleyensis. Per recruit analysis indicated that current fishing mortality reduces the L. aeneus spawner biomass by 7 %, which is considered negligible. Labeobarbus kimberleyensis forms an insignificant proportion of anglers catches and stock status is currently considered pristine.
Keywords: Barbus aeneus; Largemouth bass; Labeobarbus; Fishing -- South Africa -- Gariep Dam